Muligheter og utfordringer ved å introdusere kjernekraft som en del av energisystemet i Finnmark, med hensyn til FNs bærekraftsmål og overgangen til en lavkarbonøkonomi - En interdisiplinær analyse av små modulære reaktorer i Finnmark - Kvale, Nicholas Strand (The University of Bergen, 2024)
Opportunities and Challenges of Introducing Nuclear Energy as Part of the Energy System in Finnmark: A Sustainable Development Perspective. This thesis investigates the potential of Small Modular Reactors (SMRs) as an alternative energy source in Finnmark, emphasizing their alignment with the United Nations' Sustainable Development Goals (SDGs) and the transition to a low-carbon economy. By applying an interdisciplinary framework, the study evaluates SMR technology through economic, environmental, and social lenses, highlighting its potential to address energy demands while considering regional challenges. Data were collected through a mixed-methods approach, combining qualitative insights from focus group interviews with key stakeholders in Hammerfest, observations from a four-month internship at Norsk Kjernekraft AS, and scenario analysis of future energy strategies. The results indicate that SMR technology offers significant advantages, such as reduced land use, stable energy supply, and potential economic growth for Finnmark. However, concerns about waste management, public acceptance, and the nascent stage of SMR technology present barriers that require careful consideration. The findings underline the importance of inclusive and transparent decision-making processes, particularly regarding indigenous rights and environmental risks. By integrating theories such as Responsible Research and Innovation (RRI), the Collingridge Dilemma, and the Technology Acceptance Model (TAM), the thesis demonstrates the complex interplay between technological innovation and societal needs. Ultimately, the research contributes to understanding how SMR technology can serve as a sustainable energy solution in regions like Finnmark, balancing innovation with social and environmental accountability. Praksisbasert masteroppgave SDG351 MAHF-SDG